2015
DOI: 10.7567/jjap.54.030216
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Cu direct bonding by metal salt generation bonding technique with organic acid and persistence of reformed layer

Abstract: In this study, the effect of the metal salt generation bonding technique on the strength of a direct-bonded copper–copper interface was investigated. Copper surfaces were modified by boiling in several types of organic acids, and direct bonding was performed at a bonding temperature of 423–673 K under a load of 588 N (for a bonding time of 0.9 ks). As a result of the surface modification, bonded joints were obtained at bonding temperatures of 150 K (after treatment with formic acid) and 100 K (after citric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The combined use of hydrazine, copper­(II) acetate, and ethylene glycol were important to achieve the high-concentration synthesis of sub-10-nm Cu NPs in this synthesis. For example, large aggregates of Cu NPs were formed when we used copper­(II) formate as the replacement for copper­(II) acetate in the synthesis (not shown), although copper­(II) formate has been often used for the synthesis of Cu NPs due to the volatile and self-reducing properties of formate anions. Propylene glycol is well-known as a typical polyol solvent, but large aggregates of Cu NPs were formed when we used propylene glycol as the replacement for ethylene glycol in the synthesis (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The combined use of hydrazine, copper­(II) acetate, and ethylene glycol were important to achieve the high-concentration synthesis of sub-10-nm Cu NPs in this synthesis. For example, large aggregates of Cu NPs were formed when we used copper­(II) formate as the replacement for copper­(II) acetate in the synthesis (not shown), although copper­(II) formate has been often used for the synthesis of Cu NPs due to the volatile and self-reducing properties of formate anions. Propylene glycol is well-known as a typical polyol solvent, but large aggregates of Cu NPs were formed when we used propylene glycol as the replacement for ethylene glycol in the synthesis (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A dicing process was then carried out, and the samples were diced into the top (6 × 6 mm 2 ) and bottom (15 × 15 mm 2 ) dies. The bonding surfaces were cleaned with a citric acid [23,24] and DI water, and blown dry through an N 2 purge. The reason for this is that the native oxide layer on the bonding interface, acting as a barrier for atomic diffusion, may critically affect its bonding quality.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it was found that by modifying the Cu/Sn bonding surface with formic acid, it was possible to fabricate a base metalbreaking joint in Sn at a bonding temperature as low as 40 K. 12) It was found that by modifying the Cu bonding surface with formic acid or citric acid, it was possible to fabricate joints with the same bonding strength as those without treatment, even at a 150 K lower bonding temperature. 13) It was found that the modification treatment using formic acid on the bonding surface of SUS304 stainless steel improved the bonding strength to about twice that of the case where no treatment was applied. 14) It was found that the bonding strength was greatly improved by inserting a highpurity Al sheet with a formate film at the bonding interface between pure Ti.…”
Section: Introductionmentioning
confidence: 98%
“…However, it has been pointed out that an oxide film and a processed layer exist on the actual bonding surface, and these inhibit solid-state bonding. 13) Therefore, in order to form a connection portion having high bonding strength, it is necessary to remove the oxide film on the bonding surface. Therefore, a method for removing a surface oxide film using ultrasonic vibration 47) or a plasma processing 811) has been studied.…”
Section: Introductionmentioning
confidence: 99%